Examination about the Relation of Meal Form, Tongue Pressure, Grip and Walking State in Inpatient and Elderly Residents - TAKEDA, Yoshie; YAMADA, Kaori; TANAKA, Yoko; YOKOO, Madoka; NAKANO, Yuko; KAYASHITA, Jun (The Japanese Journal of Dysphagia Rehabilitation, 2015)
Objectives:　From a viewpoint of quality of life for patients with dysphagia, it is important to pay attention to the forms and physical properties of foods and choose foods and cooking methods suited to the ability of each patients. In hospital, medical staffs determine which food form to serve patients. However, a suitable judgment may be unable to be made at home or in institutions without a specialist. In this study, the association between tongue pressure and food form and the associations among food form, grip and walking state were determined to examine whether they may serve as criteria for the food form selected for patients.Methods:　Of the inpatients in the Saiseikai Hiroshima Hospital and the residents in the Long-Term Care Health Facility Hamanasou, 201 elderly (36 men and 165 women) were included, following informed consent. The survey consisted of tongue pressure, grip, walking state, and food form.Results:　Tongue pressure and grip of the patients who were eating nomal diet showed the value lower than those of the patients who were eating adjusted foods. There was a significant positive correlation between tongue pressure and grip. For tongue pressure, there was no difference between men and women in the patients who ate the same food form. However, grip values were significantly higher in the male patients than the female patients, even when they took the same food form. Although there was no correlation between age and tongue pressure, there was a negative correlation between age and grip. According to walking ability, both the tongue pressure and grip values were significantly higher in the subjects who could walk, as compared with the subjects who used a wheelchair or the subjects who were confined to the bed; the same values were significantly higher in the subjects who used a wheelchair compared with the subjects who were confined to the bed.Thus, associations between grip and tongue pressure and food form were found, which suggests that these values may be effective indicators for the determination of food form. However, grip was observed the sex difference and the age difference. Therefore, tongue pressure which does not require consideration of age or sex, could be used as a simple and easy indicator. Furthermore, walking ability was associated with food form. Consequently, we suggest that tongue pressure and walking ability might be useful indicators to determine the appropriate food form to serve.